2016
DOI: 10.1186/s40001-016-0229-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety of outpatient anterior cervical discectomy and fusion: a systematic review and meta-analysis

Abstract: BackgroundAnterior cervical discectomy and fusion (ACDF) is one of the most prevalent spine surgeries and neurosurgical procedures performed to treat a variety of disorders in the cervical spine. Over the last several years, ACDF has been done in the outpatient setting for less invasive approaches and exposures, as well as modified anesthetic and pain management techniques. Despite the fact that it may be innocuous in other parts of the body, complications in the spine can literally be fatal. The objective of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Similarly, from their study, Samuel et al 26 concluded that the most common cause of readmission after ACDF was non-surgical site-related issues. Furthermore, Samuel et al 26 and Ban et al 2 stated that pneumonia, dysphagia, and hemorrhage/hematoma are prominent causes of readmission after ACDF, which correlates to the results of our study; we found these conditions to be the next-largest causes of readmission after single-level ACDF (Table 2). Organ-space SSI and a swelling, mass, or lump in the neck were found in equal numbers to be the cause of readmission after single-level CDR (Table 2).…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, from their study, Samuel et al 26 concluded that the most common cause of readmission after ACDF was non-surgical site-related issues. Furthermore, Samuel et al 26 and Ban et al 2 stated that pneumonia, dysphagia, and hemorrhage/hematoma are prominent causes of readmission after ACDF, which correlates to the results of our study; we found these conditions to be the next-largest causes of readmission after single-level ACDF (Table 2). Organ-space SSI and a swelling, mass, or lump in the neck were found in equal numbers to be the cause of readmission after single-level CDR (Table 2).…”
Section: Discussionsupporting
confidence: 80%
“…17,24,35 Additionally, Ban and colleagues performed a meta-analysis and systematic review, including articles and 1693 treated levels, which revealed an overall complication rate of 1.71% and a risk ratio of 0.99, suggesting no statistical difference between inpatient and outpatient groups. 6 There may be a longer-term negative effect of outpatient ACDF. Arshi et al examined more than 12,000 patients in a private insurance database and reported that outpatient ACDF was associated with higher odds of repeat anterior surgery at 1 year (OR 1.46) as well as a higher likelihood of undergoing posterior surgery at 6 months and 1 year (ORs 1.58 and 1.79, respectively).…”
Section: Anterior Cervical Discectomy and Fusionmentioning
confidence: 99%
“…Numerous studies have verified the safety of outpatient ACDF surgery. 3,4,6,19,24,28,33,34,36 The procedure performed in an ambulatory setting is not inferior to inpatient surgery in terms of mortality, 30-day emergency department visit rates, 30-day readmission rates, and 30-day reoperation rates and is less costly than inpatient ACDF in terms of actual costs and 90-day bundled charges. 25 Nonetheless, a recent risk-complication analysis of studies on cervical spine surgery performed in ambulatory surgery centers has revealed that at least some of these studies demonstrated an inherent conflict of interest and did not report major morbidity and mortality rates for outpatient procedures in a nonbiased way, which must be considered.…”
Section: Complicationsmentioning
confidence: 99%